Persepsi Konsumen Terhadap Teh Daun Kelor 'Keloruma' Sebagai Inovasi Mahasiswa Wirausaha Merdeka dalam Pengembangan Produk Herbal Lokal - Vani Nor Hidayati; Siti Aisyah (Determinasi: Jurnal Penelitian Ekonomi Manajemen dan Akuntansi, 2026)
This study focuses on the development of local herbal products in the form of "Keloruma" moringa leaf tea as a result of student innovation in the Independent Entrepreneurship program. The purpose of this study was to determine consumer perceptions and responses to the "Keloruma" moringa leaf tea product in terms of taste, price, packaging, and perceived health benefits. The research method used was a descriptive qualitative approach with data collection techniques through semi-structured interviews with five consumers who had consumed the product. The results showed that consumers gave generally positive responses to the Keloruma product, especially in terms of affordable prices and health benefits such as a fresher body and more stable blood pressure. However, several suggestions for improvement were submitted by consumers, such as adding flavor variants and improving the packaging design to make it more attractive and informative. These findings indicate that the innovation of the moringa leaf tea product has great potential to be further developed as a functional product based on local herbs.